Global optimization using automatic differentiation: Application to quantum chemistry - Masmoudi, Mohamed; Massat, Christine; Poteau, Romuald (Zielona Góra: Uniwersytet Zielonogórski)
We present a new optimization method and one of its applications in quantum chemistry. The problem is to find the most stable configurations of sodium clusters. We have to minimize a weighted sum of eigenvalues of the Hamiltonian operator which corresponds to the energy of the molecules. According to the Rellich theorem, the eigenvalues/eigenvectors are analytic when the matrix follows an analytic path.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka